solve for x. 3(x-2)+5(x+3)=33

Question

Asked 11/15/2011 12:04:56 PM

Updated 2/19/2015 10:20:31 PM

1 Answer/Comment

Flagged by Andrew. [2/19/2015 10:20:28 PM]

f
freestar.config.enabled_slots.push({ placementName: 'weegy_incontent_1', slotId: 'weegy_incontent_1' });

Question

Asked 11/15/2011 12:04:56 PM

Updated 2/19/2015 10:20:31 PM

1 Answer/Comment

Flagged by Andrew. [2/19/2015 10:20:28 PM]

Rating

8

3(x - 2) + 5(x + 3) = 33;

3x - 6 + 5x + 15 = 33;

8x + 9 = 33;

8x = 33 - 9;

8x = 24;

x = 24/8;

x = 3

3x - 6 + 5x + 15 = 33;

8x + 9 = 33;

8x = 33 - 9;

8x = 24;

x = 24/8;

x = 3

Added 2/19/2015 10:20:31 PM

This answer has been confirmed as correct and helpful.

solve for x. x+20=-15 **Weegy:** x = -35 **User:** solve for x. 5x-4=26 **User:** 5x-4=26 **Weegy:** Sir/Madam, 5x - 4 = 26
5x = 26 + 4
5x = 30
5x/5 = 30/5
x= 6 **User:** solve for x. 9x+4=8x+5 **Weegy:** Sir/Madam, please solve 9x-15/4=x 9X - 15/4 = X subtract 1 X from each side 8X - 15/4 = 0 add 1/5/4 to each side 8X = 15/4 ( to divide the fraction 15/4 by 8 invert and ... [ ] (More)

Question

Expert Answered

Updated 6/21/2014 12:55:33 PM

2 Answers/Comments

x + 20 = -15;

x = -15 - 20;

x = -35

x = -15 - 20;

x = -35

Added 6/21/2014 12:55:06 PM

This answer has been confirmed as correct and helpful.

9x + 4 = 8x + 5;

9x - 8x = 5 - 4;

x = -1

9x - 8x = 5 - 4;

x = -1

Added 6/21/2014 12:55:33 PM

This answer has been confirmed as correct and helpful.

9x+4=8x+5

Question

Updated 7/22/2014 3:59:50 PM

1 Answer/Comment

9x + 4 = 8x + 5;

9x - 8x = 5 - 4;

x = 1

9x - 8x = 5 - 4;

x = 1

Added 7/22/2014 3:59:49 PM

This answer has been confirmed as correct and helpful.

solve for x. 12x-3=8x+9

Question

Updated 6/21/2014 12:52:39 PM

2 Answers/Comments

12x-3=8x+9 The answer is x = 3

Added 2/4/2014 9:44:31 AM

This answer has been confirmed as correct and helpful.

12x-3=8x+9;

12x - 8x = 9 + 3;

4x = 12;

x = 12/4;

x = 3

12x - 8x = 9 + 3;

4x = 12;

x = 12/4;

x = 3

Added 6/21/2014 12:52:39 PM

This answer has been confirmed as correct and helpful.

12x-3=8x+9

Question

Updated 8/27/2014 2:53:58 AM

1 Answer/Comment

12x-3=8x+9

12x-3= 9-8x

4x - 3 = 9

4x = 9 + 3

4x = 12

x = 12/4

x = 3

12x-3= 9-8x

4x - 3 = 9

4x = 9 + 3

4x = 12

x = 12/4

x = 3

Added 8/27/2014 2:53:58 AM

This answer has been confirmed as correct and helpful.

solve for x. 8(x+3)=7(x+3)

Question

Updated 10/9/2016 9:23:51 PM

1 Answer/Comment

8(x + 3) = 7(x + 3)

8x + 24 = 7x + 21

8x + 24 = 21 - 7x

x + 24 = 21

x = 21 - 24

x= - 3

8x + 24 = 7x + 21

8x + 24 = 21 - 7x

x + 24 = 21

x = 21 - 24

x= - 3

Added 10/9/2016 9:23:49 PM

This answer has been confirmed as correct and helpful.

39,505,378

questions answered

There are no comments.